Price Analysis of MSMEs on Purchasing Decisions of A&R Juice MSMEs - Yolanda Sihaloho (MultiTech Publisher, 2024)
This research aims to analyze the impact of pricing on the purchasing decisions of A&R Juice MSMEs. The research method used is qualitative, with data collection conducted through interviews with MSME actors. The results of this study indicate that if there is an increase in the pricing variable, then the purchasing decision variable will also experience an increase. This means that the pricing strategy applied can enhance purchases in the A&R Juice MSMEs, where pricing pressure is achieved through product diversification or variation. However, it is necessary to conduct a risk analysis to minimize errors in product diversification.